1953
DOI: 10.1001/jama.1953.02940290013005
|View full text |Cite
|
Sign up to set email alerts
|

Surgery by Direct Vision in the Open Heart During Hypothermia

Abstract: The heart for centuries was suspected of being a delicate organ; the slightest injury was said to be uniformly fatal. Both the great Billroth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
7

Year Published

1954
1954
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(30 citation statements)
references
References 7 publications
0
23
0
7
Order By: Relevance
“…For that reason inflammable gases and the use of relaxants and controlled 9r even assisted respirations are, avoKted. Although there is considerable argumeat for controlled and even vigorous hyperventllation in the literature (7,8), to prevent acldemia, presumably from CO2 accumulation, oex observations, from the above technique, do not bear this argument out. It seems reasonable to suppose that under light ~,naesthesia in the absence o[ known respiratory depressants, CO2 productmn parallels O2 utihzation, and that respirations at least down to 26~ are adequate to clear CO2.…”
Section: Resultsmentioning
confidence: 97%
“…For that reason inflammable gases and the use of relaxants and controlled 9r even assisted respirations are, avoKted. Although there is considerable argumeat for controlled and even vigorous hyperventllation in the literature (7,8), to prevent acldemia, presumably from CO2 accumulation, oex observations, from the above technique, do not bear this argument out. It seems reasonable to suppose that under light ~,naesthesia in the absence o[ known respiratory depressants, CO2 productmn parallels O2 utihzation, and that respirations at least down to 26~ are adequate to clear CO2.…”
Section: Resultsmentioning
confidence: 97%
“…Hypothermia also allowed the surgeons to work in better surgical conditions (arrest of circulation, empty heart, extreme bradycardia) for a longer time. The method adopted by Swan [12] was the most widely used: body temperature was progressively reduced by immersion in a cold water bath, and the patient was subsequently rewarmed by immersion in hot water. The anaesthesia management of hypothermic patients required the consideration of important metabolic and haemodynamic effects resulting from significant variations in body temperature, such as fatal arrhythmias, clotting disturbances, bleeding, and neurological injuries.…”
Section: Cardiac Anaesthesia Before the Advent Of Cardiopulmonary Bypmentioning
confidence: 99%
“…The number of articles contained in the clinical literature of the past five years attests to the increased interest in hypothermia as an adjunct to cardiac surgery. Cookson et al (9,10), Swan et al (11), and Lewis and Taufig (12) have already rendered some of their surgical patients hypothermic and report a fair degree of success with this procedure.…”
Section: IImentioning
confidence: 99%
“…The actual term, fibrillation, originated in 1875. That year Vulpian (2) reported that the application of an intense faradic current to the ventricle of a curarized or chloralosed dog produced 11 une sorte de tremblotement musculaire 11 which was very rapid and lasted for three or four minutes. This was followed by a progressive transformation into "une tremulation fibrillaire 11 • Si.…”
mentioning
confidence: 99%
See 1 more Smart Citation